2015
DOI: 10.1080/02699931.2015.1015967
|View full text |Cite
|
Sign up to set email alerts
|

Networks of prospective thoughts: The organisational role of emotion and its impact on well-being

Abstract: Recent research has shown that many prospective thoughts are organized in networks of related events, but the relational dimensions that contribute to the formation of such networks are not fully understood. Here we investigated the organizational role of emotion by using cues of different valence for eliciting event networks. We found that manipulating the emotional valence of cues influenced the characteristics of events within networks, and that members of a network were more similar to each other on affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
12
0
3
Order By: Relevance
“…Recently, Pillemer and colleagues () suggested that existing definitions of episodic autobiographical memories should also include mental representations of specific events that happened to other people. The present findings provide further support to this position and extend it by showing that either personal or public event memories can impact well‐being and that memories of those public events are organized in memory networks just like other personal memories (Demblon & D'Argembeau, ). Moreover, those networked memories can further influence well‐being and mental health symptoms, independently of how the personal or public floods‐related memory was encoded.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Recently, Pillemer and colleagues () suggested that existing definitions of episodic autobiographical memories should also include mental representations of specific events that happened to other people. The present findings provide further support to this position and extend it by showing that either personal or public event memories can impact well‐being and that memories of those public events are organized in memory networks just like other personal memories (Demblon & D'Argembeau, ). Moreover, those networked memories can further influence well‐being and mental health symptoms, independently of how the personal or public floods‐related memory was encoded.…”
Section: Discussionsupporting
confidence: 80%
“…Participants were provided with three textboxes, but were instructed that they could describe as many networked memories as they wished, up to three. This procedure has been used in past research on memories and memory networks (e.g., Demblon & D'Argembeau, ; Philippe et al, ; Philippe, Koestner, Lecours, et al, ; Philippe, Lecours, & Beaulieu‐Pelletier, ). Some participants described at least one other natural disaster event as networked memories (34.4%), but most described other types of events (which did not occur during the present floods) as various as accidents, loss of important possessions, death of a close relative, difficult romantic breakups, buying or moving to a new house, or political events .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When constructing a future episode people typically access general personal knowledge before generating episodic details (40), organize episodic future thoughts into event clusters that reflect the influence of higher-order schematic, conceptual, and affective knowledge (4142), and indicate a stronger subjective sense of “pre-experiencing” for future events that are associated with personal goals than for those that are not (43). Thus the construction of episodic details and integration of those details with higher-order autobiographical knowledge may represent distinct components of episodic future thinking (43).…”
Section: Mechanisms Of Episodic Future Thinkingmentioning
confidence: 99%
“…Such episodic simulation conveys great adaptive value by eliciting the emotional impact that a future episode might hold (4)(5)(6). However, dwelling on the future can also be detrimental to our well-being.…”
mentioning
confidence: 99%